Sectarianism in Punjab, Pakistan: A Neglect of Adab al-Ikhtilāf in Contemporary Religious Discourse - Shafique, Sohaib; Sadaf, Ayesha; Wahidah, Evita Yuliatul; Ali, Rehana Mureed; Zulqarnain, Hafiz (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2026)
The study examines the concept of sectarianism within the framework of adab al ikhtilāf (the ethics of disagreement) and finds that this phenomenon is not only a political or security issue but also an ethical and intellectual dilemma in the debate over religion today in the state of Punjab, Pakistan.  Although doctrinal diversity (ikhtilāf) has always been a legitimate and structured feature of Islamic scholarship, rooted in epistemic humility, sincere intention (Ikhlas), and community solidarity (jamāʾah), there has been a gradual breakdown of these moral checks in modern sectarian discourse.  Addressing this analytical gap, the study posed the following question: How does classical Islamic scholarship regulate disagreement, and to what extent are these principles visible in, or absent from, the religious discourse of Punjab today? Using qualitative, doctrinal, and analytical methods, the research reconstructs the classical ethical framework, grounded in Qur'anic, prophetic, and jurisprudential sources, and applies it critically to contemporary sectarian narratives in Punjab. The results indicated that sectarian polarization in Punjab is not due primarily to theological differences but to a systematic neglect of the ethical principles that have historically governed legitimate disagreement. This study proceeds in two interrelated stages. Firstly, it builds a classical Islamic ethical system for disagreement by reading and analyzing primary sources. Secondly, it argues that reviving adab al‑ikhtilāf offers a tradition‑based model for principled religious pluralism by reconnecting normative Islamic ethics with the study of contemporary sectarian discourse.